Unraveling the intra-species genomic diversity of sweetpotato-infecting CRESS-DNA and RNA viruses in Burkina Faso using Oxford Nanopore sequencing - Name, Pakyendou E.; Tibiri, Ezechiel B.; Tiendrébéogo, Fidèle; Sawadogo, Seydou; Djigma, Florencia; Traoré, Lassina; Eni, Angela O.; Pita, Justin S. (Frontiers in Microbiology, 2026)
Sweetpotato is a key crop for global food security, particularly in Burkina Faso, where its productivity is increasingly threatened by viral diseases, especially those caused by CRESS-DNA viruses. However, the diversity of these viruses in Burkina Faso remains poorly characterized due to limitations of conventional diagnostic approaches. In this study, nanopore sequencing was used to investigate the diversity of CRESS-DNA viruses infecting sweetpotato in Burkina Faso. Ninety-eight symptomatic dried leaf samples from a previously established biobank were selected and analyzed. Total DNA was extracted, enriched using rolling circle amplification (RCA), and sequenced using the MinION Mk1C platform. In parallel, RNA viruses were also investigated using nanopore sequencing. RCA successfully amplified 53 of the 98 samples, from which 28 complete and 25 partial CRESS-DNA virus genomes were recovered. Sequence analyses revealed high genomic diversity, with sweet potato leaf curl virus (SPLCV) being the most prevalent. Sweet potato symptomless virus 1 (SPSMV-1) was detected for the first time in Burkina Faso in a co-infection with SPLCV. Additionally, 52 deltasatellite genomes (50 complete, 2 partial) were identified in association with SPLCV, displaying approximately 86% nucleotide identity with known sequences, suggesting the presence of genetically distinct putative deltasatellites. RNA virome analysis revealed frequent co-infections involving sweet potato feathery mottle virus (SPFMV) and sweet potato chlorotic stunt virus, with SPFMV commonly co-occurring with SPLCV. Four complete SPFMV genomes were recovered and clustered within phylogroup B, forming a distinct subclade. Overall, this study highlights the remarkable diversity of viruses infecting sweetpotato in Burkina Faso and reports, for the first time, the presence of SPSMV-1 and sweepovirus-associated deltasatellites in the country. These findings underscore the importance of ongoing molecular surveillance to support effective viral disease management strategies and food security.